2022
DOI: 10.1111/infa.12497
|View full text |Cite
|
Sign up to set email alerts
|

Infant regulation during the pandemic: Associations with maternal response to the COVID‐19 pandemic, well‐being, and socio‐emotional investment

Abstract: In the transition to parenthood, the COVID‐19 pandemic poses an additional strain on parental well‐being. Confirmed infections or having to quarantine, as well as public health measures negatively affect parents and infants. Contrary to previous studies mainly focusing on the well‐being of school‐aged children and their parents during lockdown periods, the present study investigated how mothers of infants respond to the COVID‐19 pandemic and whether this is related to maternal well‐being, maternal socio‐emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Prior research on COVID-19 and families has revealed disproportionate negative outcomes for mothers compared to fathers. During the pandemic, mothers were found to be at significant risk of developing mental health issues (internalizing problems), such as depression and anxiety, especially during pregnancy [ 27 , 28 , 29 ]. Mothers also self-reported more instances of feeling lonely and anxious, and yelling at their children, than fathers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on COVID-19 and families has revealed disproportionate negative outcomes for mothers compared to fathers. During the pandemic, mothers were found to be at significant risk of developing mental health issues (internalizing problems), such as depression and anxiety, especially during pregnancy [ 27 , 28 , 29 ]. Mothers also self-reported more instances of feeling lonely and anxious, and yelling at their children, than fathers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sperber et al (2023) found that the more US mothers reported disruptive life events related to COVID-19, the more they experienced anxiety, depression, and stress when their infants were 12 months old and anxiety and depression when their infants were 24 months old. Likewise, Reinelt et al (2023) found that among a sample of high-SES mothers from Switzerland, those who had a maladaptive response to the pandemic also experienced a decrease in overall well-being.…”
mentioning
confidence: 97%
“…Likewise, Reinelt et al. (2023) found that among a sample of high‐SES mothers from Switzerland, those who had a maladaptive response to the pandemic also experienced a decrease in overall well‐being.…”
mentioning
confidence: 98%
See 2 more Smart Citations